2004
DOI: 10.1177/107906320401600303
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Impact of Polygraphy on High-Risk Behaviors in Adult Sex Offenders

Abstract: This study examined whether polygraph testing would result in sex offenders engaging in fewer high-risk behaviors. Fifty adult male sex offenders taking part in community treatment programs were allocated into 2 groups: "Polygraph Aware" subjects were told they would receive a polygraph examination in 3 months regarding their high-risk behaviors, while "Polygraph Unaware" subjects were told their behavior would be reviewed in 3 months. Relevant behaviors for each subject were established at baseline interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 9 publications
3
41
0
Order By: Relevance
“…In thirteen studies it was reported that some/all of the participants were also receiving (inpatient and outpatient) psychological therapy (O'Connell, 1997;Stovering, Nelson, & Hart., 2013;Heil, Ahlmeyer, & Simons, 2003;Van Arsdale et al, 2012;Cook et al, 2014;McGrath et al, 2007;English et al, 2003;English et al, 2000;Schenk et al, 2014;Kokish et al 2005;Grubin et al, 2004;Grubin & Madsen, 2006;Buschman et al, 2010). However, one study controlled for these treatment effects in the analysis by comparing a treatment only with a combined polygraph treatment group (McGrath et al, 2007).…”
Section: Removal Of Duplicates= 22 Hitsmentioning
confidence: 99%
See 4 more Smart Citations
“…In thirteen studies it was reported that some/all of the participants were also receiving (inpatient and outpatient) psychological therapy (O'Connell, 1997;Stovering, Nelson, & Hart., 2013;Heil, Ahlmeyer, & Simons, 2003;Van Arsdale et al, 2012;Cook et al, 2014;McGrath et al, 2007;English et al, 2003;English et al, 2000;Schenk et al, 2014;Kokish et al 2005;Grubin et al, 2004;Grubin & Madsen, 2006;Buschman et al, 2010). However, one study controlled for these treatment effects in the analysis by comparing a treatment only with a combined polygraph treatment group (McGrath et al, 2007).…”
Section: Removal Of Duplicates= 22 Hitsmentioning
confidence: 99%
“…Two studies explored selfreported accuracy and utility from a single intervention design (Kokish et al, 2005;Grubin & Madsen, 2006). Four studies followed a quasi-experimental design with a polygraph intervention and comparison group, (McGrath et al, 2007;Gannon et al, 2014;Cook et al, 2014;Schenk et al, 2014); others included a polygraph unaware group (Grubin et al, 2004), a between samples comparison, i.e. parolee vs. prisoner (Heil et al, 2000;Heil, Ahlmeyer, & Simons, 2003), or a within subjects comparison between multiple polygraphs (Ahlmeyer et al, 2000).…”
Section: Removal Of Duplicates= 22 Hitsmentioning
confidence: 99%
See 3 more Smart Citations